47.9k views
0 votes
What is the solution to the following system

What is the solution to the following system-example-1
User Octopoid
by
5.7k points

2 Answers

0 votes

Answer:

C. Is you answer

Explanation:

What you have to do is you take the second equation and plug it into the y of the first equation to get

-2x^2+-3x^2+5=-5. You will then add the -2x^2 and the -3x^2 together to get

-5x^2+5=-5. You will then minus the 5 from both sides to get

-5x^2=-10. You will then divide the -5 from both sides to get

x^2=2. You will then square root it to get

x=sqrt2 and -sqrt2.

You will then plug the sqrt2 into the second equation into the x like this

y=-3(sqrt2)^2+5. and you answer wil be -1.

So C is your answer.

User Steveyang
by
5.3k points
3 votes

C is the answer.............

User Jwueller
by
6.3k points